Sepsis associated encephalopathy and abdominal sepsis: current state of problem - Shuliatnikova, T. V.; Shavrin, V. O.; Шулятнікова, Тетяна Володимирівна; Шаврін, Володимир Олександрович (My University, 2018)
The aim of the work is to analyze literature data on the current status of sepsis and sepsis associated encephalopathy (including against background of abdominal sepsis). For this purpose, 59 scientific publications of PubMed, Google Scholar and Research Gate scientific platforms were retrospectively analyzed. Із метою аналізу даних літератури щодо сучасного стану питань сепсису і сепсис асоційованої енцефалопатії (в тому числі на тлі абдомінального сепсису) проаналізовано 59 наукових публікацій наукових платформ PubMed, Google Scholar та Research Gate.
Сепсис асоційована енцефалопатія та абдомінальний сепсис: поточний стан проблеми
Keywords: sepsis associated encephalopathy; abdominal sepsis; сепсис асоційована енцефалопатія; абдомінальний сепсис